Penerapan Pendekatan Keterampilan Proses Pada Materi Getaran Dan Gelombang Terhadap Hasil Belajar Mahasiswa Pendidikan Fisika IKIP PGRI Pontianak - Angraeni, Lia; Trisianawati, Eka (Berkala Ilmiah Pendidikan Fisika, 2017)
The purpose of this study was to determine: 1) the average student results given experimental class learning approach process skills; 2) the average student results given control class learning to use the conventional approach 3) whether there is a difference in student learning outcomes after a given learning approach and process skills using conventional approaches. This study design is quasi-experimental design. Data collection techniques used is a measurement technique .. Based on data analysis that uses the learning process skills approach to the learning outcomes of students on the material vibrations and waves both categories. Thus the detailed conclusions are as follows; 1) average student results given experimental class learning with good process skills approach; 2) Average grade student results are given learning control using conventional approaches is sufficient; 3) There are significant differences anatara student results after a given learning approach and process skills given student learning using the conventional approach.Â